2016
DOI: 10.1002/rhc3.12106
|View full text |Cite
|
Sign up to set email alerts
|

Living With the Invisible Risks in the U.S. Urban Areas: Potential Nuclear Power-Induced Disasters, Urban Emergency Management Challenges, and Environmental Justice Issues

Abstract: This article attempts to understand potential risks of nuclear power emergencies associated with the U.S. commercial nuclear power plants (NPPs), which could impact populations living within a 50‐mile radius around NPPs during a nuclear disaster. This article will first examine the demographic composition of the populations in communities that host NPPs in urban and non‐urban areas in 1990, 2000, and 2010. Second, the study will investigate the distributive justice of the potential risks, by looking into the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The treatment of time or temporality within current energy justice research is inconsistent, however. This is despite a lengthy history of consideration by parallel disciplines including environmental and climate justice (e.g., Kyne, ; Page, ). As an illustration, Sidortsov and Sovacool (, p. 306) state that “energy justice is best understood by examining instances of injustice” and that “it is unlikely that one would take note of how just and fair things are unless something disturbs the status quo.” In this regard they highlight a tendency to look back in time, take an evaluative approach, and focus on the remediation of past injustice.…”
Section: Multinational Energy Justicementioning
confidence: 99%
See 1 more Smart Citation
“…The treatment of time or temporality within current energy justice research is inconsistent, however. This is despite a lengthy history of consideration by parallel disciplines including environmental and climate justice (e.g., Kyne, ; Page, ). As an illustration, Sidortsov and Sovacool (, p. 306) state that “energy justice is best understood by examining instances of injustice” and that “it is unlikely that one would take note of how just and fair things are unless something disturbs the status quo.” In this regard they highlight a tendency to look back in time, take an evaluative approach, and focus on the remediation of past injustice.…”
Section: Multinational Energy Justicementioning
confidence: 99%
“…Of course, multinational energy negotiations with inter and intra‐generational elements already occur for a range of reasons, be it security and proliferation, resource trading or skill share (see Findlay, ; Fischhendler, Herman, & Anderman, ; Herron & Jenkins‐Smith, ; Kyne, ; Liping, ; Taebi & Mayer, ; Wieczorek, Raven, & Berkhout, ). Kuipers et al () highlight plentiful scholarship in the crisis and disaster literatures that engage with nuclear risk (and more specifically with citizen engagement, communication, and regulation) (see also Chien, ; Kuipers & Welsh, ), but this scholarship does not explicitly address the multinational aspects of nuclear risks and, thereby, also does not engage with the questions of multinational justice (Goldthau & Sovacool, )…”
Section: Multinational Energy Justicementioning
confidence: 99%
“…e Chaves et al's study compares crowdsourcing tools designed for urban planning and urban emergency management and proposes five-dimensional types of crowdsourcing quality that can be used to optimize urban planning and emergency management processes [2]. Kyne applied the definition of pesticides in American law to urban management research, and he compared the pesticidal model to urban disasters to discuss [3]. It can be found that although many scholars have proposed appropriate models, they can often only evaluate one kind of disaster.…”
Section: Related Workmentioning
confidence: 99%